KINERJA GURU AGAMA HINDU BERBASIS BUDAYA RELIGIUS MORAL - I Nyoman Sueca (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2017)
Religious culture is a movement carried out by religion, from the process of human interaction with a doctrine that has been believed by society is a performance of religious teachers to instill budhi pekerti to learners, so that cultural relations with religion is the integrity of a person or group.Given the religious school culture held by principals, teachers, administrative staff, and students will bring a dominant value supported by the school.School culture consists of values, beliefs, knowledge, and traditions, ways of thinking, and behavior that are all different from other social institutions.School culture is a very important component to promote a positive school and can pay attention to mothers fathers, teachers, and other students. School activities are still often done by the school as a form of moral religious culture such as; culture greetings, wall magazines, interactive dialogue, siplin culture, hard work culture, creative culture, and independent culture.Keywords: Performance of religion-based religious teachers.